The role of titin in eccentric muscle contraction - Herzog, W. (The Journal of Experimental Biology, 2014)
been thought to occur exclusively through the relative sliding of and the interaction between the contractile filaments actin and myosin. While this two-filament sarcomere model has worked well in explaining the properties of isometrically and concentrically contracting muscle, it has failed miserably in explaining experimental observations in eccentric contractions. Here, I suggest, and provide evidence, that a third filament, titin, is involved in force regulation of sarcomeres by adjusting its stiffness in an activation-dependent (calcium) and active force-dependent manner. Upon muscle activation, titin binds calcium at specific sites, thereby increasing its stiffness, and cross-bridge attachment to actin is thought to free up binding sites for titin on actin, thereby reducing titin`s free-spring length, thus increasing its stiffness and force upon stretch of active muscle. This role of titin as a third force regulating myofilament in sarcomeres, although not fully proven, would account for many of the unexplained properties of eccentric muscle contraction, while simultaneously not affecting the properties predicted by the twofilament cross-bridge model in isometric and concentric muscle function. Here, I identify the problems of the two-filament sarcomere model and demonstrate the advantages of the three-filament model by providing evidence of titin`s contribution to active force in eccentric muscle function.